1987
DOI: 10.1073/pnas.84.16.5788
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor type beta induces monocyte chemotaxis and growth factor production.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
626
2
9

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,123 publications
(661 citation statements)
references
References 31 publications
20
626
2
9
Order By: Relevance
“…To quantify the amplified transcripts, PCR was conducted by incorporation at 14-34 cycles using cDNA samples from FLS. The amounts of amplified products of MCAF and &m were exponential at [14][15][16][17][18][19][20][21][22][23][24][25][26] cycles and then decreased slowly (data not shown); PCR amplification of cDNA for MCAF and &m was consequently carried out for 20 cycles in this study. As shown in Figure 5 , 188 bp of MCAF transcripts were detected in FLS incubated with the medium alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify the amplified transcripts, PCR was conducted by incorporation at 14-34 cycles using cDNA samples from FLS. The amounts of amplified products of MCAF and &m were exponential at [14][15][16][17][18][19][20][21][22][23][24][25][26] cycles and then decreased slowly (data not shown); PCR amplification of cDNA for MCAF and &m was consequently carried out for 20 cycles in this study. As shown in Figure 5 , 188 bp of MCAF transcripts were detected in FLS incubated with the medium alone.…”
Section: Resultsmentioning
confidence: 99%
“…Transforming growth factor p (18,19) and granulocyte-macrophage colony-stimulating factor (GM-CSF) (20), both present in SF and synovial tissue of patients with RA, are active chemotactic factors for monocytes. The components of complement are also monocyte chemoattractants.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that TGF-,B1 administered over a protracted period of time can significantly suppress the proliferative activity in the small intestinal crypts, the effect being particularly pronounced in the stem cell region . In addition, TGF-ps can have the opposite effect on some cell types and act as indirect mitogens, particularly for mesenchymal cell types, and exert effects on chemotaxis and on the synthesis and degradation of extracellular matrix proteins (Ignotz and Massague 1986;Posthlethwaite et al, 1987;Wahl et al, 1987;Roberts and Sporn, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It can be hypothesized that this could be due to a direct activity of the transgenic TGF␤1 on these cells. It has been observed before that this factor can be chemoattractant on human peripheral blood monocytes 21 and that it is also able to induce migratory gut-seeking lymphocytes to become resident within the intraepithelial compartment of the gut. 22,23 It is also possible that the accumulation of apoptotic cells that would result from the activity of the transgene on secretory hyperplastic lesions could attract mononuclear cells to the area.…”
Section: Weak Wap-tgf␤1 Tumor Inhibitory Effect May Be a Consequence mentioning
confidence: 96%